Mechanical characterization of the structural components of Pre-Columbian earthen monuments: Analysis of bricks and mortar from Huaca de la Luna in Perú - Aguilar R. (2017)
This research was carried out by the Engineering & Heritage Research Group at PUCP. The authors would like to acknowledge the Pontificia Universidad Católica del Perú PUCP and its funding office DGI-PUCP (project 89-2014) for providing funds to the project within which this work was developed. The authors would also like to thank the fellowship funding for postgraduate studies for the second author by CONCYTEC, PERU (Contract N° 012-2013-FONDECYT). The authors finally acknowledge the support of the Laboratory of Materials at PUCP for providing access to their facilities and equipment.